Comparison of 18F-Choline PET/CT and 99mTc-Sestamibi SPECT/CT in the Localization of Hyperactive Parathyroid Glands in Primary Hyperparathyroidism: Diagnostic Performance in Discordant Cases - Kang, Sungkeun; Cho, Hojin; Kim, Eunjin; Kim, Jin Kyong; Kang, Sang-wook; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woungyoun (Frontiers in Endocrinology, 2025)
IntroductionAccurate localization of hyperactive parathyroid glands is essential in managing primary hyperparathyroidism. Despite advances in imaging, discordant findings still complicate surgical planning. Tc-99m-sestaMIBI SPECT/CT (MIBI SPECT/CT) and 18F-Choline PET/CT (FCH PET/CT) are commonly used, particularly when localization is discordant.ObjectiveThis study compared the findings of FCH PET/CT and MIBI SPECT/CT with intraoperative outcomes in patients who underwent parathyroidectomy for primary hyperparathyroidism. In discordant cases, the relative diagnostic performance and postoperative outcomes of the two modalities were analyzed.Materials and methodsWe retrospectively reviewed 133 patients who underwent parathyroidectomy between January 2020 and December 2024 and had both MIBI SPECT/CT and FCH PET/CT. Patients were classified according to concordance between imaging and surgical localization: Group 1 (both modalities concordant), Group 2 (MIBI concordant only), Group 3 (FCH concordant only), and Group 4 (both discordant). Diagnostic performance (sensitivity and PPV) and biochemical cure—defined as normalization of parathyroid hormone (PTH) and calcium at 6 and 12 months—were compared between Groups 2 and 3.ResultsOf 133 patients, 82 (61.7%) were in Group 1, 5 (3.8%) in Group 2, 37 (27.8%) in Group 3, and 9 (6.8%) in Group 4. Sensitivity and PPV were 74.4% and 86.1% for MIBI, and 97.5% and 91.5% for FCH PET/CT, respectively. The biochemical cure rate was 80.0% vs 94.6% at 6 months and 50.0% vs 87.5% at 12 months for Groups 2 and 3, with calcium levels remaining within the normal range. Preoperative PTH levels and chief-cell proportions were higher in Group 3 (91.9%) than in Group 1 (82.6%).DiscussionFCH PET/CT demonstrated better diagnostic performance and higher cure rates than MIBI SPECT/CT in discordant cases. Although differences were not statistically significant, they may be influenced by preoperative parathyroid activity and histologic composition.ConclusionFCH PET/CT showed a trend toward improved diagnostic performance and postoperative cure compared with MIBI SPECT/CT in discordant cases. While not superior in all situations, it can complement MIBI SPECT/CT and enhance surgical decision-making in complex clinical settings.